2019
DOI: 10.1111/jdv.15641
|View full text |Cite
|
Sign up to set email alerts
|

The evolution of healthy skin to acne lesions: a longitudinal, in vivo evaluation with reflectance confocal microscopy and optical coherence tomography

Abstract: Background Comedogenesis is defined as the process of the development of a new comedo, which is of great importance for the understanding of acne. Objective To evaluate the formation and evolution of acne lesions from clinically unaffected skin of patients with mild–moderate acne to characterize the morphological changes and natural resolution by means of in vivo reflectance confocal microscopy (RCM) and dynamic optical coherence tomography (D‐OCT). Methods Ten patients with mild–moderate acne, not assuming an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
84
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(89 citation statements)
references
References 25 publications
0
84
0
5
Order By: Relevance
“…10,12,15 The clinical application of D-OCT includes assistance in differential diagnosis for selected skin lesions and noninvasive monitoring of treatment effects, especially for inflammatory skin conditions with alterations of blood flow. [16][17][18] A recent study has reported morphologic and vascular characteristic of subclinical AD with an angiographic OCT. 9 Despite there being many studies of the effects of dupilumab on AD disease activity to our knowledge, there are no studies which describe the microscopic and functional changes associated with a systemic therapy.…”
mentioning
confidence: 99%
“…10,12,15 The clinical application of D-OCT includes assistance in differential diagnosis for selected skin lesions and noninvasive monitoring of treatment effects, especially for inflammatory skin conditions with alterations of blood flow. [16][17][18] A recent study has reported morphologic and vascular characteristic of subclinical AD with an angiographic OCT. 9 Despite there being many studies of the effects of dupilumab on AD disease activity to our knowledge, there are no studies which describe the microscopic and functional changes associated with a systemic therapy.…”
mentioning
confidence: 99%
“…[77] The following failure of terminal differentiation of follicular corneocytes participates to hyperkeratinization, one of the main factors contributing to acne comedogenesis. [78] Alteration of sebum lipid composition can be involved in impaired barrier function of the infundibular epithelium and comedone generation in acne skin. For example, oleic acid has been reported to regulate human keratinocyte differentiation, as well as to have comedogenic abilities in rabbit auricular skin.…”
Section: Cell Proliferation/differentiation Rate Correlated To Andrmentioning
confidence: 99%
“…[ 77 ] The following failure of terminal differentiation of follicular corneocytes participates to hyperkeratinization, one of the main factors contributing to acne comedogenesis. [ 78 ]…”
Section: Hypothesis: Altered Cell Differentiation Is Linked To Dysregmentioning
confidence: 99%
“…Manfredini M. et al [ 5 ] assessed the evolution of acne lesions from clinically unchanged skin in mild to moderate acne patients using in vivo reflection confocal microscopy (RCM) and dynamic optical coherence tomography (D-OCT). After analyzing seventy complete sets of clinical pictures comrpising RCM and D-OCT, it was shown that the appearance of an acne lesion is preceded by the growth of large follicles in the area corresponding to funnel keratinization.…”
Section: Introductionmentioning
confidence: 99%